Requirements of industrial revolution 4.0 for higher education in Vietnam - Hoàng Thanh Xuân; Nguyễn Ngọc Trường (Tạp chí Nghiên cứu Khoa học Công đoàn, 2020)
This article is not ambitious (and cannot) summarize to give a full assessment of the status of Vietnamese higher education, in order to answer the question of industrial revolution 4.0. What are the requirements for Vietnamese higher education? But just outline some shortcomings of Vietnamese higher education (related to the requirements of the industrial revolution 4.0); On that basis, a number of solutions are proposed to renovate higher education in Vietnam today to meet the requirements of the industrial revolution 4.0.